Strengthening Paradiplomacy for Migrant Worker Protection: The Collaboration Between Riau Islands Province and Johor State (2019–2024) - Anshari, Muhammad Ilham; Mahfudin, Irvan Aladip (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the paradiplomatic collaboration between the Riau Islands Provincial Government and the State of Johor in safeguarding Indonesian migrant workers (PMI) from 2019 to 2024. As a critical gateway for Indonesian labor migration to Malaysia, the Riau Islands face ongoing challenges in providing adequate protection for migrant workers, particularly within border regions. Using David Criekmans' framework on paradiplomacy, this research explored the dynamics, challenges, and limitations of the cooperative efforts between these sub-national governments. The study employed a descriptive qualitative methodology, drawing on document analysis and case studies to provide a comprehensive understanding of the actions undertaken. The findings highlight significant barriers to effective collaboration, including (1) insufficient political representation and coordination between the two sub-national governments; (2) central government dominance in decision-making, limiting local authority; (3) bilateral agreements that inadequately address migrant worker protection; and (4) constrained sub-national diplomatic efforts under central government oversight. These factors impeded the ability of the Riau Islands Province and Johor State to act as pivotal actors in resolving migrant worker-related challenges. This research contributed to the discourse on paradiplomacy by identifying the structural and operational shortcomings in cross-border collaboration for migrant worker protection, offering insights for strengthening sub-national cooperation in similar contexts.